Do Individual Differences in Cognition and Personality Predict Retrieval Practice Activities on MOOCs? - Fellman, Daniel; Lincke, Alisa; Jonsson, Bert (Frontiers in Psychology, 2020)
Online quizzes building upon the principles of retrieval practice can have beneficial effects on learning, especially long-term retention. However, it is unexplored how interindividual differences in relevant background characteristics relate to retrieval practice activities in e-learning. Thus, this study sought to probe for this research question on a massive open online course (MOOC) platform where students have the optional possibility to quiz themselves on the to-be-learned materials. Altogether 105 students were assessed with a cognitive task tapping on reasoning, and two self-assessed personality measures capturing need for cognition (NFC), and grittiness (GRIT-S). Between-group analyses revealed that cognitively high performing individuals were more likely to use the optional quizzes on the platform. Moreover, within-group analyses (n=56) including those students using the optional quizzes on the platform showed that reasoning significantly predicted quiz performance, and quiz processing speed. NFC and GRIT-S were unrelated to each of the aforementioned retrieval practice activities.